Positive thinking training in reducing stress for people with hypertension - Aulia, Risca; Widyana, Rahma (Universitas Mercu Buana Yogyakarta, 2022)
One of the causes of hypertension is stress, and non-pharmacological interventions can be given to decrease stress levels so that blood pressure could also be reduced. The intervention provided in this study was positive thinking training. This study aimed to find out the influence of positive thinking training in reducing the stress levels of people with hypertension, by using a pretest-posttest randomized control group design with three meausurement points. The subjects of the study consisted of 10 people with hypertension who are in moderate to severe scores (based on the Indonesian version of the Depression Anxiety Stress Scales), and analyzed with the Mann-Whitney non-parametric test. The results indicated a significant difference (p<0.05) in positive thinking training in reducing stress between the experimental group and control group. Next, a non-parametric Wilcoxon signed rank test was applied. Results indicated a significant difference Z = -2,032 (p<0,050) in the stress levels of people with hypertension before and after positive thinking training. This study has implications for positive thinking training applications in reducing the stress of people with hypertension. It was concluded that positive thinking training can reduce the stress of people with hypertension.